Biodiversity and Transportation Infrastructure in the Republic of Korea: A Review on Impacts and Mitigation in Developing the Country - Desiree Andersen (MDPI AG, 2021)
The construction and continued use of transportation infrastructure, specifically roads, has had a significant global impact on biodiversity and the environment. The Republic of Korea, or South Korea, has a road density of 1.13 km/km2. So far, three nationwide studies about vertebrate road-killed species have been reported, showing bias towards medium to large mammals, the most common victims being the Korean water deer (Hydropotes inermis), Korean hare (Lepus coreanus), Siberian roe deer (Capreolus pygargus), and the common raccoon dog (Nyctereutes procyonoides). Road-kills, or wildlife-vehicle collisions (WVCs), tend to occur in or near preferred habitat types or in highly fragmented areas, with roads additionally being linked to habitat fragmentation and loss. Alongside WVCs and habitat effects, information about other adverse effects on biodiversity is scant, although there are reports that heavy metals and other pollutants from road runoff impact marine biodiversity, vegetation, soil, and groundwater. Furthermore, roads have been linked to a prevalence of invasive plant species. To mitigate road impacts, the South Korean government has constructed, with mixed results, 530 wildlife crossing structures, mainly including overpasses and tunnels. To mitigate road impacts more effectively, the country will need more construction, monitoring, and consistent management of wildlife crossing structures. Further, incorporating plans for wildlife crossing structures in early stages of road development will be required.